Financial literacy and financial well-being: A mediation analysis of fintech services adoption among selected generation Z in Metro Manila - Abad, Justine Marie M. (Animo Repository, 2023)
The study aimed to investigate the mediating role of payment and non-payment fintech services in the effect of financial literacy on financial well-being among 158 Generation Z individuals in Metro Manila. Drawing on the Rational Choice Theory, the study employed the Financial Literacy Assessment questionnaire to measure financial literacy, the Consumer Financial Protection Bureau (CFBP) Financial Well-being Scale to assess financial well-being, and actual frequency of usage to assess financial technology (fintech) adoption. Causal mediation analysis was used to analyze the data, revealing that financial literacy has a positive effect on financial well-being. However, it does not significantly influence the adoption of fintech, whether payment-or non-payment-related. Furthermore, the study found that the adoption of fintech, regardless of its type, does not directly affect financial well-being or mediate the relationship between financial literacy and financial well-being. The findings also highlighted the high adoption rate for payment fintech, contrasting with the low adoption rate for non-payment fintech. These findings emphasized the need to consider financial literacy as a fundamental life skill. It also underscores the importance of integrating digital finance into financial literacy education and highlights the necessity for the development of holistic digital financial management tools. Keywords: Financial Literacy, Financial Well-Being, Payment Fintech Adoption, Non-Payment Fintech Adoption, Causal Mediation Analysis, Generation Z